Four-Electron Reduction of Oxygen Electrocatalyzed by a Mixture of Porphyrin Complexes onto Glassy Carbon Electrode - Aguirre-Quintana, M; Aguirre-Quintana, M (Electrochemical Science Group, 2018)
In this work a new composite electrode for the electrocatalytic reduction of oxygen (ORR) is presented. For this purpose, glassy carbon electrodes (GC) were modified with CoII and FeIII octaethylporphyrins. The system that presents the highest electrocatalytic activity towards ORR is GC modified with a mixture of both octaethylporphyrins in 1:1 volume proportion (GC Co-Fe 1:1) over the GC electrodes modified with CoII and FeIII octaethylporphyrins separately. This modified electrode can reduce O2 through two reduction processes (four electrons each), by the generation of H2O as final product, in two active sites of different chemical nature. All the electrodic systems were morphologically characterized by atomic-force microscopy (AFM) and electrically characterized by electrochemical impedance spectroscopy (EIS). It was found that the electroactive system (GC Co-Fe 1:1) presents high differences on its surface and performs the lowest charge transfer resistance (Rct) in comparison to the rest of the modified systems and GC itself. © 2018 The Authors.